IMPLEMENTASI E-PROCUREMENT DI UNIVERSITAS DIPONEGORO - Ndikron, Ndikron; Suryaningsih, Margaretha; Santoso, R Slamet (Journal of Public Policy and Management Review, 2016)
The massive case of corruption in procurement of goods and services encourage the government to publish new policy named e-procurement .E-procurement considered the government able to overcome the problems in procurement as cases of corruption, Diponegoro University as institutions college also implement e-procurement in the need procurement of goods and services, but in the application faces obstacles and makes the implementation not be optimal. Problems underlying as deficiency human resources, incompleteness supporting facilities, as well as lack of readiness the target group is the major cause. This report is written with research methodology qualitative and description aimed at know the state of the implementation of e-procurement and know by factors in support and inhibitors of of e-procurement. The result of this research when viewed from the effectiveness of the implementation not yet optimal because it is still the low understanding the target group and the factors barrier namely the resources and bureaucratic structure of the actor e-procurement policy at the Diponegoro University. Based on the outcome of this research recommended to do improve the quality of related to the procurement of goods and services by means of .Informed to the target group about actor implementor, do maintenance on the software and hardwere at regular intervals , inviting people to apply supervision , improvement of infrastructure , do recruitmen staff as well as fix jobdesk staff.